Clinical pharmacokinetics and pharmacodynamics of ivosidenib in patients with advanced hematologic malignancies with an IDH1 mutation - Fan, Bin; Dai, David; DiNardo, Courtney D.; Stein, Eytan; de Botton, Stéphane; Attar, Eyal C.; Liu, Hua; Liu, Guowen; Lemieux, Ian; Agresta, Samuel V.; Yang, Hua (Cancer chemotherapy and pharmacology, 2020)
Purpose Isocitrate dehydrogenase (IDH) mutations lead to formation of the oncometabolite 2-hydroxyglutarate (2-HG), which is elevated in several solid and liquid tumors. Ivosidenib (AG-120) is a targeted, potent, oral inhibitor of the mutant IDH1 protein. We describe detailed pharmacokinetics and pharmacodynamics of ivosidenib in patients with advanced hematologic malignancies with an IDH1 mutation treated in a phase I study (ClinicalTrials.gov NCT02074839). Methods Patients received single and multiple oral doses of ivosidenib from 100 mg twice daily to 1200 mg once daily (QD) in 28-day continuous cycles. Concentrations of ivosidenib and 2-HG in plasma, and 2-HG in bone marrow, were assessed at routine intervals. Plasma 4β-hydroxycholesterol/cholesterol ratios were assessed as a marker of CYP3A activity. Results Ivosidenib was rapidly absorbed and slowly eliminated (half-life 72–138 h) after single and multiple dosing. Ivosidenib exhibited dose- and time-dependent pharmacokinetics, with exposure increasing sub-proportionally to dose, and clearance increasing with increasing dose. Plasma 2-HG concentrations were maximally and persistently inhibited in the majority of patients receiving 500-mg QD ivosidenib, to concentrations close to those observed in healthy subjects. Ivosidenib pharmacokinetics were not affected by mild or moderate renal impairment, mild hepatic impairment, age, weight, sex, race, or co-administration of weak CYP3A4 inhibitors or inducers. Moderate-to-strong CYP3A4 inhibitors decreased ivosidenib clearance. Ivosidenib also induced CYP3A enzyme activity, with increases in 4β-hydroxycholesterol/cholesterol ratios of 119–168% at 500-mg QD ivosidenib. Conclusions Ivosidenib 500-mg QD has favorable pharmacokinetic and pharmacodynamic profiles in patients with advanced hematologic malignancies with an IDH1 mutation. Clinical trial registration ClinicalTrials.gov NCT02074839.